POSFUST RELIABILITY OF A NON-REPAIRABLE MULTI-STATE SYSTEM WITH POSFUST FAILURE RATE ESTIMATION - Harendra Yadav; Mukesh Kumar Sharma; Vishnu Narayan Mishra (The Journal of Engineering and Exact Sciences)
Present research paper attempts to estimate the posfust reliability of a non-repairable multi-state system (NRMSS). Failure rate estimation is key factor in the reliability estimation. But due to uncertainty in the environment and probabilistic measure, the absolute measurement of the failure rate is quite tedious. In this research paper, we have introduced a new measure for failure rate estimation using possibilistic measure based on fuzzy logic. In this work for the effective measurements of reliability, we have tried to cover the uncertainty in the failure rate at every state failure level. In this research paper, we have taken a non-repairable three state system and failure rate transition of every state is taken in the form of upper and lower bound in possibilistic measure.  In this approach, Markov process (multi-state system) is used for getting the governing differential equation for transition from one state to another state. Numerical computations are also being carried out to estimate the posfust reliability.